Morphological features of adenohypophysis stillborn from HIV-infected mothers. - Sherstiuk, S. A.; Sorokina, I. V. (Морфологія / Morphologia / Morfologìâ, 2012)
Adenohypophysis stillborn from HIV-infected mothers had a high functional stress for long periods of fetal development, leading to inhibition of its functional state, as evidenced by the decrease in the diameter of cells, reducing their secretory granules, and increased nuclear-cytoplasmic index. In the antenatal period of development in the adenohypophysis of stillbirths from HIV-infected mothers apparently failed embryogenesis, which appeared violation of a population growth of acidophilic cells. Inhibition of functional activity of the entire population of cells of the adenohypophysis indicate a failure of compensatory possibilities of the body, which in future may be the cause of severe endocrinopathies.